Course of COPD Assessment Test (CAT) Scores During Bacterial Exacerbations of Chronic Obstructive Pulmonary Disease Treated in Outpatient Setting - Jordan Minov; Jovanka Karadzinska-Bislimovska; Kristin Vasilevska; Saso Stoleski; Mijakoski, Dragan (Bentham Science Publishers Ltd., 2015)
Introduction: COPD Assessment Test (CAT) is an 8-items questionnaire for assessment of health status in patients with chronic obstructive pulmonary disease (COPD). Objective: To evaluate the course of CAT scores during bacterial exacerbations of COPD treated in outpatient setting. Methods: We performed an observational, prospective study including 81 outpatients (57 males and 24 females, aged 43 to 74 years) with bacterial exacerbation of COPD. All participants completed CAT at initial visit (i.e. at the time of diagnosis of exacerbation and beginning of its treatment), 10 and 30 days after initial visit. Mean scores of each item, as well as the overall mean score, at these time points were compared. Results: The mean scores for each CAT question at initial visit varied from 2.6 to 3.5, whereas the mean scores for each CAT question 10 days after initial visit varied from 1.7 to 2.6. We registered significant reduction of the mean overall CAT score 10 days after initial visit as compared to its value at initial visit of 6.9 ± 2.7 points (16.8 vs 23.7; P < 0.001). The mean scores for each CAT question 30 days after initial visit varied from 1.3 to 2.4. We registered reduction of mean overall CAT score 30 days after initial visit as compared to its score 10 days after initial visit of 2.9 ± 1.2 points (13.9 vs 16.8; P < 0.005). The mean overall CAT score 30 days after initial visit was reduced for 9.8 ± 4.5 points as compared to its value at initial visit (13.9 vs 23.7; P < 0.001). Conclusion: We found significant improvement in the patient’s health status during recovery from exacerbation as compared to their health status at the time of exacerbation confirming the CAT as an effective tool to measure health status in patients with COPD.
Keywords: Chronic obstructive pulmonary disease; Exacerbation; Health status; Questionnaire; Score